Gender and Employment Structure Patterns in Australia’s Retail Workforce: An Intra-industry Analysis - Chang, Joshua; Travaglione, Antonio (National Institute of Labour Studies, 2012)
Challenging conditions in Australian retail pose a threat to its retail workforce and are expected to change the retail employment landscape. This prompts a need to develop a contemporary knowledge of the retail workforce, which has a higher incidence of insecure employment than the general workforce. This study investigates gender and employment-structure patterns between different sectors within the retail industry by analysing the variables of employment status and gender between 40 Australian and New Zealand Standard Industrial Classification (ANSIC) retail categories (for example groceries, clothing, automobiles, hardware, restaurants), using data from the ‘Australia at Work’ survey. The results show that while overall women dominate employment in the retail sector, retail employment among women tends to be part-time and lower-skilled, while men tend to be in more physical, skilled, prestigious, and full-time positions. Societal gender expectations such as the breadwinner role for men and child caring for women are also identified.